2009
DOI: 10.1007/s10815-009-9329-3
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies and other perinatal outcomes in ICSI vs. naturally conceived pregnancies: a comparative study

Abstract: Background Intracytoplasmic sperm injection (ICSI) procedures have become accepted worldwide and their effect on society is well-known. However, the full extent of the possible complications of these procedures on maternal and neonatal outcome is still unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…A large Australian study obtained from three registries in western Australia found that 8.6% of infants who were conceived with ICSI had a major birth defect, as compared with naturally conceived infants (OR for a major birth defect, 2; 95% CI = 1.3-3.2); however, in this study anomalies included were those reported up to 1 year of age [7]. A retrospective study from Saudi Arabia found a similar incidence of congenital fetal malformations [11], and similarly a Belgian study found no increased incidence of congenital malformations in ICSI children [12]. However, other studies did not show this increase.…”
Section: Discussioncontrasting
confidence: 55%
“…A large Australian study obtained from three registries in western Australia found that 8.6% of infants who were conceived with ICSI had a major birth defect, as compared with naturally conceived infants (OR for a major birth defect, 2; 95% CI = 1.3-3.2); however, in this study anomalies included were those reported up to 1 year of age [7]. A retrospective study from Saudi Arabia found a similar incidence of congenital fetal malformations [11], and similarly a Belgian study found no increased incidence of congenital malformations in ICSI children [12]. However, other studies did not show this increase.…”
Section: Discussioncontrasting
confidence: 55%
“…Of note, the potential negative impact of micromanipulation techniques should be considered, but only a few research studies have made precise distinctions between IVF and ICSI pregnancies [11,12,14]. …”
Section: Discussionmentioning
confidence: 99%
“…This fact can be explained partly by the high rate of multiple pregnancies as a result of these procedures, and by advanced maternal age [10], but past research has also focused on the potential negative impact of micromanipulation techniques, extended culture systems, and medications used in the context of IVF/ICSI [11,12]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single embryo transfer is now promoted which has reduced these complications. Despite this ART children still have a higher perinatal morbidity and mortality than matched controls (Al-Fifi et al, 2009;Helmerhorst et al, 2004). A systematic review found that for singletons the relative risk of a very preterm birth (<32 weeks) was 3.27 (95% CI 2.03 -5.28) after assisted conception (Helmerhorst et al, 2004).…”
Section: Adverse Perinatal Outcomesmentioning
confidence: 99%